STUDI TUTUPAN KARANG DI DESA SITARDAS KECAMATAN BADIRI KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA Study of Life form Coral in Stardas Village Tapian Nauli Sub district, District of Tapanuli Tengah, Sumaterea - Harry Muda Hasibuan; Hasan Sitorus; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Sitardas Village at Badiri sub district, District of Tapanuli Tengah is one of conservesion area that potensial tourism and fhisiries at Districtof Tapanuli Tengah. The aims of the study are to analize the percentage of coral covered area.The research was conducted for two months from April to Agust 2014 in Stradas Village. The research used survey method by using Line Intercept Transect (LIT) in two research stations with line transect 100 meters and three replications in each transect. Guildelines for measuring the condition of coral refers to Bapeda Regulation No. 47 of 2001. The results showed the condition of coral reefs in the Stardas Village was middle health category with coral covered area of 27,53%. The result dicreased compared to monitoring conducted by Marine and Fisheries Department of North Sumatera in, 2014 (50,96%), and 2015 (34.06%). The highest lifeform coral percentages in first station was Dead Scleractinia with a persentation of 34 %and than the highest lifeform coral percentages in second station was Hard Coral (Acropora) to cover a persentation of 44.4 %.Keywords : Coral Covered Area, Sitardas Village, Tapanuli Tengah District